Microencapsulation of Garlic Oil with Gelatin and Maltodextrin Encapsulant Using the Coacervation Method - Fitriyani, Elisa; Damayantia, Anastasia Devina; Ruwaidaha, Listia Aulia; Nabila, Shifa Annisa; Fadilah, Fadilah (Program studi Teknik Kimia UNS, 2023)
ABSTRACT. Garlic Oil is widely used as a raw material for fragrances with volatile active compounds at room temperature. It is easily affected by environmental changes and this problem can be solved by microencapsulation using coacervation methods to protect active compounds. Garlic Oil was encapsulated using gelatin and sodium alginate as coating materia with glutaraldehyde as the crosslinking agent. The purpose of this research was to study the effect of the composition of polymers and the mass of garlic oil on encapsulation characteristics. The resulting microcapsules were analyzed using a digital microscope, SEM, FTIR, and encapsulation efficiency. The result showed that microcapsules have an irregular shape with a textured surface. The FTIR spectrum showed an indication of garlic oil with allicin content in microcapsules. The encapsulation efficiency is 34.23% with a yield of 29.43%.Keywords: microencapsulation, coacervation, garlic oil